Secure hybrid fiber optic and free optical space communication systems - Arwa A. Moosa; Malik A. Alsaedi; Hussein Jumma Jabir; Mays Afif Anaee (Institute of Advanced Engineering and Science, 2022)
This work investigates the integration of Electrical to Optical (E/O) and Optical to Electrical (E/O) communication systems. Two ways of transition, namely, Hybrid Fiber Optic (FO) and Free Optical Space (FSO) transmission system have been proposed. This work aims to evaluate the performance of these two transition ways. FO has the optimum transmission due to its lower attenuation which can be reached to 350 km. However, for further assurance of reaching data to the receiver side a second way of transition has been investigated. FSO path has been employed under different weather conditions of clear, moderate dust, heavy dust and heavy fog. Matlab and Optisystem7 software’s have been used to simulate Optical Secure Data Transition (SDT). The results show that an optimum transmission could be obtained using FO with RGB image encryption where the Mean Square Error (MSE) reach to 9.88 ×10^7 in read channel and it can reach to 4.93 ×10^9 using Discrete Wavelet Transform (DWT).